2023
DOI: 10.1080/07853890.2023.2257711
|View full text |Cite
|
Sign up to set email alerts
|

From cold chain to ambient temperature: transport of viral specimens- a review

Oliver Christy Dsa,
Trupti Sathish Kadni,
Sudheesh N

Abstract: The diagnosis of an aetiology is dependent on the collection, transport, and storage of the infectious sample. The transport of the sample plays a crucial role in the chain of diagnosis. It is important to maintain the biological integrity of the pathogen during the transport of the sample to achieve an accurate diagnosis. This is important, particularly for labile organisms like viruses that are inactivated easily compared to other microorganisms. Many transport media have been utilised to ensure the integrit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…Despite their continued use, both VTM/UTM and MTM have limitations. One drawback of VTM/UTM is that they can only preserve live viruses for finite periods, i.e., typically 48–72 h when kept refrigerated, after which the viability of the virus significantly decreases, leading to possible false negative results [ 30 , 31 , 32 , 33 ]. Furthermore, most VTM/UTM usually require cold-chain transportation, and collected pathogens are potentially infectious, adding complexity and cost to sample handling, shipment, and transport [ 30 , 31 , 32 , 33 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite their continued use, both VTM/UTM and MTM have limitations. One drawback of VTM/UTM is that they can only preserve live viruses for finite periods, i.e., typically 48–72 h when kept refrigerated, after which the viability of the virus significantly decreases, leading to possible false negative results [ 30 , 31 , 32 , 33 ]. Furthermore, most VTM/UTM usually require cold-chain transportation, and collected pathogens are potentially infectious, adding complexity and cost to sample handling, shipment, and transport [ 30 , 31 , 32 , 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…One drawback of VTM/UTM is that they can only preserve live viruses for finite periods, i.e., typically 48–72 h when kept refrigerated, after which the viability of the virus significantly decreases, leading to possible false negative results [ 30 , 31 , 32 , 33 ]. Furthermore, most VTM/UTM usually require cold-chain transportation, and collected pathogens are potentially infectious, adding complexity and cost to sample handling, shipment, and transport [ 30 , 31 , 32 , 33 ]. Conversely, MTM contains harsh and hazardous chemicals, requires a nucleic acid extraction step, and does not maintain viral infectivity and protein structure, which is essential for virological studies, culture-based detection methods, and rapid antigen/lateral flow tests.…”
Section: Discussionmentioning
confidence: 99%
“…Several other studies have evaluated commercial transport media for their compatibility with nucleic acid testing ( 39 ). These studies have shown that PSMTM and other commercially available transport media inactivate several avian viruses as well as SARS-CoV-2 ( 14 , 17 , 23 , 39–43 ). However, nucleic acid preservation results were not available in all these studies.…”
Section: Introductionmentioning
confidence: 99%
“…Charcoal viral transport medium (CVTM) is specifically designed for the transportation of adenovirus, coxsackie virus, and herpes viruses at room temperature ( Leibovitz, 1969 ; Jensen and Johnson, 1994 ). The BD Universal Viral Transport System (UVT) has been designed to efficiently maintain HSV-1, influenza A, and RSV ( Dsa and Kadni TS, 2023 ). Additionally, PrimeStore ® MTM, an inactivated transport medium, effectively preserves the influenza A virus strain A/California/04/2009 at a temperature of 25°C for a duration of 30 days ( Schlaudecker et al., 2014 ).…”
Section: Introductionmentioning
confidence: 99%